Pengetahuan Gizi Seimbang dan Keamanan Pangan Tim Pendamping Keluarga (TPK) dalam Penurunan Stunting Desa Pejaten Kabupaten Karawang - Nurfita, Hanny Aqmarina; Aein, Muhammad Akhdiyatul; Elvandari, Milliyantri (Innovative: Journal Of Social Science Research, 2024)
The inability of children under 5 years of age to grow due to chronic malnutrition, especially in the First 1000 Days of Life (HPK), is also known as stunting. TPK as a cadre in providing additional food in posyandu activities and activities related to child health in the region should not only have knowledge related to balanced nutrition but also have knowledge related to food safety in the process of making food products that will later be given to mothers and toddlers who attend posyandu. to determine the level of knowledge of TPK Pejaten Village regarding knowledge of balanced nutrition and food safety. This study used a cross-sectional design. The respondents in this study numbered 30 respondents consisting of TPK and PKK cadres. The instrument used was a questionnaire on knowledge related to balanced nutrition and food safety. The results of the study showed that most TPK knowledge was moderate, 10 (50%). There needs to be an increase in knowledge so that TPK has good knowledge in the process of assisting families at risk of stunting in the field